Artificial Intelligence in Bangladesh’s Legal System: Pathways to Smart and Efficient Justice - Mohammad Khabbab Taki (Nusantara: Journal of Law Studies, 2026)
This study examines the integration of Artificial Intelligence (AI) into Bangladesh’s judicial system, aiming to identify pathways toward achieving Smart and Efficient Justice under the Smart Bangladesh Vision 2041. The escalating case backlog, which rose from approximately 3.68 million in 2021 to over 4.65 million by mid-2025, underscores the pressing need for timely, accessible, and efficient judicial services. The study employs a normative policy analysis combining document review and comparative literature, including the draft National Artificial Intelligence Policy (2024), the National Strategy for Artificial Intelligence (2020), and international benchmarks such as India’s e-Courts Project, the UK’s ethical AI guidelines, and Nepal’s e-justice initiatives. This approach evaluates institutional readiness and identifies gaps in policy, human resources, and technological infrastructure. Findings reveal a disconnect between ambitious AI policy frameworks and practical implementation, with key barriers including regulatory limitations, insufficient AI literacy among judicial actors, workforce shortages, and ethical concerns such as algorithmic bias, data privacy risks, and multilingual processing challenges. The study contributes a contextualized roadmap for AI adoption in Bangladesh’s judiciary, integrating global ethical standards, including UNESCO’s Recommendation on the Ethics of Artificial Intelligence, with local institutional realities. Recommendations encompass investment in multilingual AI systems, capacity-building programs, public–private partnerships, and robust governance mechanisms. These measures are expected to reduce case backlogs, enhance access for marginalized populations, and promote a more efficient, inclusive, and responsive judicial system, advancing Smart Justice in Bangladesh.